The Effect of Water Quality on Growth of Microalgaes Chlorella pyrenoidosa - Srinatalia Silaen; Welmar Olfan Basten Barat (Politeknik Negeri Batam, 2022)
The diversity of microalgae on earth is very high, the high diversity of microalgae allows us to obtain microalgae that have the potential to produce large amounts of oil. In addition, the use of microalgae as a source of biodiesel does not interfere with the food supply. This is because microalgae do not compete with food. The results of the analysis showed that the parameters that passed the water quality standard were BOD in the range of 0.990-90.76 mg/l, COD in the range of 3.093 -283 mg/l, and phosphate in the range of 0.01-0.21 mg/l. Judging from the color and smell, the waters that are closer to the cages will be greener in color accompanied by the smell of fish mixed with fishy feed and feel thick. COD content ranged from 3.093 mg/l-269.5 mg/l. This is caused by the high concentration of organic matter in the waters. The quality of the waters of Lake Toba which is classified as not good is the measurement of color, smell, taste, BOD, COD, and Phosphate in the waters. Which are classified as good temperature, turbidity, pH, Ammonia, and Nitrate. The level of fertility of the waters of Lake Toba in terms of the abundance of phytoplankton is included in the fertile category. If it is categorized at the level of pollution through the diversity index, then the waters are included in the moderately polluted category.